Nanotechnology: Consequences for Human Health & the Environment - Hester, R. E. (Royal Society of Chemistry, 2012)
This volume provides comprehensive coverage of the current issues concerning engineered nanoparticles and offers a broad overview of the sources, behavior and risks associated with nanotechnology.